50 Troponin is independently associated with increased short-term mortality in hospitalised patients with COVID-19 infection: a retrospective study in an inner city london hospital. (4th June 2021) - Shyam-Sundar, Vijay; Stein, Dan; Spazzapan, Martina; Sullivan, Andrew; Qin, Cathy; Voon, Victor
Abstract : Introduction: Increased mortality is thought to be associated with an elevated troponin in addition to co-morbidities and age. International studies have demonstrated that troponin is an independent predictor of mortality in COVID-19 patients but to our knowledge this has not been assessed in a UK hospitalised population. We performed a single-centre retrospective observational study investigating the association between troponin positivity in patients hospitalised with COVID-19 and increased mortality in the short term. Methods: All adults admitted with swab-proven RT-PCR COVID-19 to Homerton University Hospital (HUH) from 04.02.20 to 30.04.20 were eligible for inclusion. We retrospectively analysed data collected from the physical and electronic patient records (EPR) including demographic and biochemical data (e.g. serum high sensitivity Troponin I). Data was analysed according to the primary outcome of death at 28 days during hospital admission. Troponin positivity was defined above the upper limit of normal according to our local laboratory assay (>15.5ng/l for females, >34 ng/l for males). Univariate and multivariate logistical regression analyses were performed to evaluate the link between troponin positivity and death. Results: The total number of adults with swab-proven RT-PCR COVID-19 to HUH from the date of the first positive swab to 30th April 2020 was 402. Mean length of stay for all patients was 9.1 days(SD 12.0). Table 1 shows selected demographics. This is a highly comorbid population with modest ethnic minority representation. Mean age was 65.3 years for men compared to 63.8 years for women. In those with a positive initial troponin, there was a high burden of mortality at 28 days post-admission. Mortality in troponin positive and negative patients is shown in table 2 . A chi-squared test showed that survival of COVID-19 patients was significantly higher in those with a negative troponin (p = 3.23 x10-10) compared to those with a positive troponin. A Mann Whitney U test showed that initial troponin was significantly higher in those who died (p = 2.24 x10-12) compared to those who were alive. Mean initial troponin was 89.8 (95% CI 43.1 – 136.5). In the multivariate logistical regression, lung disease, age, troponin positivity and CPAP were all significantly associated with death, with an AUC of 0.8872, sensitivity of 0.9004 and specificity of 0.6292 for the model. Within this model, troponin positivity was independently associated with short term mortality (OR 3.23, 95% CI 1.53-7.16, p=0.00278). Conclusions: We demonstrated an independent association between troponin positivity and increased short-term mortality in COVID-19 in a London district general hospital. The mechanisms implicated in myocardial injury in COVID-19 are not fully understood but are likely multi-factorial. Conflict of Interest: Nil